2004
DOI: 10.1103/physrevlett.93.172501
|View full text |Cite
|
Sign up to set email alerts
|

New Half-Life Measurement ofHf182: Improved Chronometer for the Early Solar System

Abstract: The decay of 182Hf, now extinct, into stable 182W has developed into an important chronometer for studying early solar system processes such as the accretion and differentiation of planetesimals and the formation of the Earth and the Moon. The only 182Hf half-life measurements available were performed 40 years ago and resulted in an imprecise half-life of (9+/-2)x10(6) yr. We redetermined the half-life by measuring the specific activity of 182Hf based on two independent methods, resulting in a value of t(1/2)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(62 citation statements)
references
References 27 publications
1
61
0
Order By: Relevance
“…We review the situation concerning 182 Hf, which β − decays to 182 W. A greatly improved measurement ofτ182 Hf by Vockenhuber et al [266] has now establishedτ182 Hf = 12.8 ± 0. [269] and [270] was two orders of magnitude higher than reported by Harper [29].…”
Section: Hfmentioning
confidence: 99%
“…We review the situation concerning 182 Hf, which β − decays to 182 W. A greatly improved measurement ofτ182 Hf by Vockenhuber et al [266] has now establishedτ182 Hf = 12.8 ± 0. [269] and [270] was two orders of magnitude higher than reported by Harper [29].…”
Section: Hfmentioning
confidence: 99%
“…The isochron regression was done using the Isoplot 3.0 of Kenneth R. Ludwig, and the 95% confidence limit was selected as the uncertainties of the isochron. The ∆t was calculated using the relationship of ∆t = 1/λ × ln [( 182 Hf/ 180 Hf) CHUR / ( 182 Hf/ 180 Hf) GRA 95209 ], where λ = 0.0779 ± 0.0008 Myr −1 (Vockenhuber et al 2004). The upper limit of the ∆t uncertainty was assessed using the upper limit of the 182 Hf/ 180 Hf CHUR and the lower limit of the 182 Hf/ 180 Hf GRA 95209 and λ, and vice versa for the lower limit.…”
Section: Hf-w Isochron Ages Of Acapulcoites Versus Lodranitesmentioning
confidence: 99%
“…The short-lived chronometer 182 Hf-182 W, t 1/2 = 8.90 ± 0.09 million years (Vockenhuber et al 2004), has been shown to be one of the best tools for studying the metal-silicate differentiation and thermal history of early planetary bodies (Harper et al 1991;Harper and Jacobsen 1996;Halliday 1996, 1997;Horan et al 1998;Schoenberg et al 2002;Yin et al 2002;Kleine et al 2002Kleine et al , 2004Kleine et al , 2005aKleine et al , 2005bQuitté et al 2000Quitté et al , 2005Quitté and Birck 2004;Lee 2005;Markowski et al 2006aMarkowski et al , 2006b). This is due largely to the different chemical behavior between Hf and W, with Hf tending to concentrate in the silicate mantle, while W goes into the metal core during metal-silicate segregation (Lee and Halliday 1996;Kleine et al 2005aKleine et al , 2005bLee 2005;Quitté et al 2005;Markowski et al 2006aMarkowski et al , 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…The most promising of these tracers currently appears to be the 182 Hf-182 W isotope system, introduced in Section 3.2. This short-lived system (t ½ for 182 Hf = 8.9 Ma; Vockenhuber et al, 2004) can be used to trace the early fractionation of an incompatible lithophile trace element (Hf) from a highly incompatible MSE (W), as a result of processes that occurred within the first ~60 Ma of solar system history. For example, the observation that the 182 W/ 184 W of terrestrial rocks are ~200 ppm more radiogenic than chondrites (Kleine et al, 2002;Schoenberg et al, 2002;Yin et al, 2002b;Burkhardt et al, 2008) has led to the interpretation that the majority of terrestrial core formation occurred within the first 30 Ma of solar system history (Kleine et al, 2002;Yin et al, 2002b;Halliday, 2004;Kleine et al, 2009).…”
Section: Tungsten Isotopes In the Mantlementioning
confidence: 99%